2011
DOI: 10.1186/1756-0500-4-569
|View full text |Cite
|
Sign up to set email alerts
|

Modularity detection in protein-protein interaction networks

Abstract: BackgroundMany recent studies have investigated modularity in biological networks, and its role in functional and structural characterization of constituent biomolecules. A technique that has shown considerable promise in the domain of modularity detection is the Newman and Girvan (NG) algorithm, which relies on the number of shortest-paths across pairs of vertices in the network traversing a given edge, referred to as the betweenness of that edge. The edge with the highest betweenness is iteratively eliminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…For each edge in miRNA-regulated protein interaction network, we calculated its ‘Edge Betweenness’ to assess the importance of a specific interaction in the network. ‘Edge Betweenness’ is defined as the frequency of an edge that places on the shortest paths between all pairs of vertices in network [ 49 ]. The edges with highest betweenness values are most likely to lie between functional modules.…”
Section: Methodsmentioning
confidence: 99%
“…For each edge in miRNA-regulated protein interaction network, we calculated its ‘Edge Betweenness’ to assess the importance of a specific interaction in the network. ‘Edge Betweenness’ is defined as the frequency of an edge that places on the shortest paths between all pairs of vertices in network [ 49 ]. The edges with highest betweenness values are most likely to lie between functional modules.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, this high-throughput signaling pathway network study utilizing proteomic, genomic, and functional experimentation allows for a more systematic understanding of VEGF-A signaling in hypoxic and normoxic BMEPCs. Systematic studies, such as these, are valuable with the emergence of advanced computational biology geared toward understanding cell signaling networks (2,14,43,45). Interestingly, computational modeling has been used to predict outcomes of ECs during angiogenesis and suggested that VEGF-A stimulation would induce a survival and sprouting phenotype (14) observed in BM-EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Modularity has been reported to be another important aspect of an interaction network. 22 Nodes that are highly interconnected within the network are usually involved in the same biological modules or pathways. Using Markov clustering algorithm, we divided the interaction network of crucial targets of HCC differentially expressed miRNAs into four functional modules containing 97, 89, 24, and 11 nodes, respectively (Fig.…”
Section: Network Analysismentioning
confidence: 99%